2016
DOI: 10.1371/journal.pone.0148534
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Microbial Constituents of the Home Environment of Individuals with Cystic Fibrosis (CF) and Their Association with Lower Airways Infections

Abstract: IntroductionCystic fibrosis (CF) airways are colonized by a polymicrobial community of organisms, termed the CF microbiota. We sought to define the microbial constituents of the home environment of individuals with CF and determine if it may serve as a latent reservoir for infection.MethodsSix patients with newly identified CF pathogens were included. An investigator collected repeat sputum and multiple environmental samples from their homes. Bacteria were cultured under both aerobic and anaerobic conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…The introduction of ST395 during the construction of a hospital was already suspected in the United Kingdom (3). This is consistent with the frequent isolation of the ST395 clone in water (19,20) and the probable role of drinking water as a source of P. aeruginosa infection (21,22). Overall, the ST395 clone has presumably contaminated the water network of the hospital before its opening but the pathogen further spread among patients by other routes of transmission (e.g.…”
Section: Bessupporting
confidence: 74%
“…The introduction of ST395 during the construction of a hospital was already suspected in the United Kingdom (3). This is consistent with the frequent isolation of the ST395 clone in water (19,20) and the probable role of drinking water as a source of P. aeruginosa infection (21,22). Overall, the ST395 clone has presumably contaminated the water network of the hospital before its opening but the pathogen further spread among patients by other routes of transmission (e.g.…”
Section: Bessupporting
confidence: 74%
“…Given the ubiquity of P. aeruginosa in the natural environment and abundant data from more recent works [ 34 ] showing shared clonal but unrelated connected strains, we believe that the four patient-pairs with shared strains observed in our study are not due to cross-infection. We demonstrated through WGS that isolates differed much more between patients than within patients, suggesting independent environmental acquisition [ 17 , 34 , 35 ]. Our findings agree with recent evidence positing the likelihood of independent acquisition of isolates from the environment [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study assessed microbial constituents at home and found that the home environment (although rarely) can serve as either a source of infection or a persistent reservoir for reinfection. 33 …”
Section: Discussionmentioning
confidence: 99%